Electronic Media-Based Health Interventions Promoting Behavior Change in Youth: A Systematic Review. - Hieftje, Kimberly; Edelman, E Jennifer; Camenga, Deepa R; Fiellin, Lynn E (JAMA pediatrics, 2013)
IMPORTANCE Little research has been done on the efficacy of electronic media-based interventions, especially on their effect on health or safety behavior. The current review systematically identified and evaluated electronic media-based interventions that focused on promoting health and safety behavior change in youth. OBJECTIVE To assess the type and quality of the studies evaluating the effects of electronic media-based interventions on health and safety behavior change. EVIDENCE REVIEW Studies were identified from searches in MEDLINE (1950 through September 2010) and PsycINFO (1967 through September 2010). The review included published studies of interventions that used electronic media and focused on changes in behavior related to health or safety in children aged 18 years or younger. FINDINGS Nineteen studies met the criteria and focused on at least 1 behavior change outcome. The focus was interventions related to physical activity and/or nutrition in 7 studies, on asthma in 6, safety behaviors in 3, sexual risk behaviors in 2, and diabetes mellitus in 1. Seventeen studies reported at least 1 statistically significant effect on behavior change outcomes, including an increase in fruit, juice, or vegetable consumption; an increase in physical activity; improved asthma self-management; acquisition of street and fire safety skills; and sexual abstinence. Only 5 of the 19 studies were rated as excellent. CONCLUSIONS AND RELEVANCE Our systematic review suggests that interventions using electronic media can improve health and safety behaviors in young persons, but there is a need for higher-quality, rigorous interventions that promote behavior change.